PREVALENCE OF SOIL-TRANSMITTED HELMINTHIASIS AMONG ELEMENTARY CHILDREN IN SORONG DISTRICT, WEST PAPUA - Yuwono, Natalia; Husada, Dominicus; Basuki, Sukmawati (Indonesian Journal of Tropical and Infectious Disease, 2019)
Soil transmitted helminthiasis are common in the world and cause illness, especially in developing countries. It can cause infection in humans by contact with parasitic eggs or larvae that live in moist and warm soil. Soil-transmitted helminthiasis is often caused by Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale, and Necator americanus. In Indonesia, Soil transmitted helminthiasis prevalence is still high in some places. The tropical climate and high humidity support for the development of worms like in Sorong District, but there was no data. The purpose of this study is to identify the presece of Soil transmitted helminthiasis in primary school children in Sorong District. A cross-sectional study was conducted in two elementary schools located in Sorong District, West Papua, Indonesia. The two elementary schools are SDN 22 in Klain village and SD  Inpres 24 in sub-district Mayamuk. Once collected, the pot that has contained stool is given formalin 10%. Stool examinattion using direct smear method to determine the presence of soil transmitted helminthiasis. Researchers get the subject as many as 147 children. The proportion of elementary school children by sex consists of 72 boys (49%) and 75 girls (51%). The prevalence of Soil transmitted helminthiasis as a whole was 30.6% (45/147) with 40.1% (18/45) single infections and 59.9% (27/45) mixed infections. The single infection that most frequent is Trichuris trichiura, then followed by Ascaris lumbricoides. Soil-transmitted helminthiasis mostly found in girl than boy and mostly found in 6-9 years age group.  The worm species that infect elementary school children in the district is Ascaris lumbricoides, Trichuris trichiura, Hookworm, and Strongyloides stercoralis. This is probably related with the climate and low sanitation level. To eliminate soil transmitted helminthiasis among elementary school children, in addition to routine treatment also needs intensive counseling about the importance of maintaining personal hygiene and the environment.